2019
DOI: 10.3390/rel10010066
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Interaction of Buddhism and Daoism in the Tang Dynasty: Inner Cultivation and Outer Authority in the Daode Jing Commentaries of Cheng Xuanying and Li Rong

Abstract: This paper takes the different interpretations of one and the same sentences in the Daode jing as “inner cultivation” or “worldly power” respectively, in the commentaries of two closely related early Tang Daoist authors, Cheng Xuanying 成玄英 and Li Rong 李荣, as a starting point to approach the question of interaction of Buddhism and Daoism from a new angle. Instead of trying to pinpoint influences, origins, and derivatives, I propose to delineate philosophical discourses that cross the boundaries of the three tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Yan Zun's 嚴遵 Han dynasty Laozi zhigui 老子指歸 (The Essential Meaning of the Laozi) Chan 1998) and Zhong Hui's 鍾會 Wei dynasty commentary (Chan 2003) both have preliminary studies. Commentaries emerging from religious or organized Daoism are also topics of interest, including the Xiang'er 想爾 (Bokenkamp 1997;), those by Tang dynasty Chongxuan experts Cheng Xuanying and Li Rong 李榮 (Assandri 2019(Assandri , 2021, and even those that reveal the text as a manual for inner alchemy . Chinese Buddhist commentaries have received some attention with both a general review ) and a couple special investigations of the wonderful commentary by Ming dynasty monk Hanshan Deqing 憨山德清 (Hsu 1975;Yen 2004).…”
Section: Traditional Laozegetics Research In Englishmentioning
confidence: 99%
“…Yan Zun's 嚴遵 Han dynasty Laozi zhigui 老子指歸 (The Essential Meaning of the Laozi) Chan 1998) and Zhong Hui's 鍾會 Wei dynasty commentary (Chan 2003) both have preliminary studies. Commentaries emerging from religious or organized Daoism are also topics of interest, including the Xiang'er 想爾 (Bokenkamp 1997;), those by Tang dynasty Chongxuan experts Cheng Xuanying and Li Rong 李榮 (Assandri 2019(Assandri , 2021, and even those that reveal the text as a manual for inner alchemy . Chinese Buddhist commentaries have received some attention with both a general review ) and a couple special investigations of the wonderful commentary by Ming dynasty monk Hanshan Deqing 憨山德清 (Hsu 1975;Yen 2004).…”
Section: Traditional Laozegetics Research In Englishmentioning
confidence: 99%
“…Buddhism was introduced to China during the Han dynasty and influenced and interacted with traditional Chinese culture, and eventually become part of Chinese ideology (Assandri 2019;Li et al 2018). Chinese people are quite familiar with Buddhism and consider Buddhism as part of their daily lives (Guang 2013).…”
Section: Respondentsmentioning
confidence: 99%
“…For example, Bychkov (2019) studied how aesthetic observation in a religious environment can influence human belief in reality. Buddhism, known for its spirituality beyond physical reality, has differed significantly from Western rational positivism (Hummel 2010;Assandri 2019). Scholars argue that Buddhist values teach a way of understanding real life, such as life suffering (Fuderich 2007), compassion (Kraft 1992), and inner peace (Lee et al 2013) and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng Xuanying's Daode jing yishu is representative for this philosophical trend. A close study of the text (Assandri 2021b) reveals that it not only integrates Madhyamaka logic, but incorporates many other Buddhist concepts. In fact, Daoism of the Sui and early Tang in Changan had incorporated many Buddhist concepts, as the Benji jing also shows.…”
Section: Introductionmentioning
confidence: 99%
“…This approach aims to add to the existing approaches for studying Tang philosophy across the boundaries of the three teachings: Methodologically, the earliest approaches relied on microhistory with the study of individual thinkers, including Buddhists, Daoists, and mid-and late-Tang Confucian thinkers. Such a focus on single thinkers suggested, in many cases, that adherence to one teaching did not preclude engagement with the teachings of the others (Emmerich 1987;Barrett 1992;Hamar 1999;Yu 2000;Cheng 2003;Qiang 2006;Höckelmann 2016;Makeham 2018a;Assandri 2021b). Using a larger framework, studies of Daoist chongxuanxue of the sixth and seventh centuries showed how Daoist authors engaged with Buddhist concepts and ideas (Lu 1993(Lu , 1997Yu 2000;Qiang 2002a;Li 2005;Assandri 2009;Cheng 2009;Hong 2020).…”
Section: Introductionmentioning
confidence: 99%